ARE WARNING COLORS HANDICAPS - Guilford, T; Dawkins, M (1993)
The handicap theory, in which the cost of waste guarantees honest advertising, is being used increasingly in solutions to the problems of biological signal evolution. The ability of the handicap theory to explain the design of signals has never been properly tested. The authors test its ability to explain signal design features in warning coloration and mimicry. Since a full handicap model proves immediately unrealistic, they modify the model to incorporate realistic assumptions about predator learning. Using this model they explicitly compare the handicap theory with a purely "conventional' signalling model and with a null model. Predictions relating to three key design features (conspicuousness, pattern similarity, and Batesian minmicry) are compared, and tested against available data. Although many predictions remain to be tested adequately, the authors conclude that: 1) conspicuousness is most plausibly explained by the conventional signalling theory that ascribes the function of conspicuous coloration to signal efficacy rather than waste; 2) pattern similarity, within and between species, is unlikely to be the result of the need to produce similar degrees of conspicuousness, as predicted by the handicap theory, but is plausibly explained as the result of pattern generalization amongst discriminating predators, as predicted by the conventional signalling theory; and 3) Batesian mimicry is predicted by the conventional signalling theory, but not the handicap theory. The handicap theory thus fails to provide an adequate explanation of the main design features of at least one major signalling system. -from Authors